Tumor cell-derived osteopontin promotes tumor fibrosis indirectly via tumor-associated macrophages - Yuying Tan; Yong-Guang Yang; Xiaoying Zhang; Lei Zhao; Xiaocong Wang; Wentao Liu (Journal of Translational Medicine)
Abstract Background High fibrosis of the tumor microenvironment (TME) not only impedes the effective infiltration of T cells but also serves as a physical barrier to inhibit the penetration of chemotherapy drugs. Triple-negative breast cancer (TNBC) is characterized by significant infiltration of tumor-associated macrophages (TAMs) and high fibrosis. However, the mechanism of high fibrosis in such tumors is still under debate. Methods We first investigated the correlation between tumor-derived osteopontin (OPN) and tumor fibrosis as well as TAM enrichment using a tumor model characterized by OPN genetic inactivation or overexpression. We further compared the effects of macrophage depletion on tumor fibrosis in mice bearing TNBC tumors (4T1 WT or 4T1 Spp1 − KO ). To elucidate the mechanism by which TAMs promote tumor fibrosis, we evaluated their potential to recruit cancer-associated fibroblasts (CAFs) through in vitro migration assays and compared the production of transforming growth factor-beta 1 (TGFβ1) among different TAM subpopulations. Results Our study revealed that OPN secretion by tumor cells correlates positively with both tumor fibrosis and TAM enrichment. Specifically, within the enriched TAM population, Ly6C+CD206− TAMs recruit CAFs via CCL5 secretion, while Ly6C−CD206high TAMs secrete TGFβ1 to activate CAFs. Blocking the tumor cell-derived OPN can effectively prevent tumor fibrosis. Conclusions This study shows that tumor-derived OPN primarily drives TAM enrichment in mouse cancer model, indirectly promoting tumor fibrosis through Ly6C+CD206−/low and Ly6C−CD206high TAMs. Our findings have potential application in preventing tumors from excessive fibrosis and enhancing the efficacy of immunotherapy and chemotherapy.